Production of π+, π-, K+, K -, p, and p̄ in light (uds), c, and b jets from Z0 decays - Abe, K; Abe, K; Abe, T; Adam, I; Akimoto, H; Aston, D; Baird, K; Baltay, C; Band, H; Barklow, T; Bauer, J; Bellodi, G; et al. (2004)
We present improved measurements of the differential production rates of stable charged particles in hadronic Z0 decays, and of charged pions, kaons, and protons identified over a wide momentum range using the SLD Cherenkov ring imaging detector. In addition to flavor-inclusive Z0 decays, measurements are made for Z0 decays into light (u, d, s), c, and b primary flavors, selected using the upgraded vertex detector. Large differences between the flavors are observed that are qualitatively consistent with expectations based upon previously measured production and decay properties of heavy hadrons. These results are used to test the predictions of QCD in the modified leading logarithm approximation, with the ansatz of local parton-hadron duality, and the predictions of three models of the hadronization process. The light-flavor results provide improved tests of these predictions; the heavy-flavor results provide complementary model tests. In addition we have compared hadron and antihadron production in light quark (as opposed to antiquark) jets. Differences are observed at high momentum for all three charged hadron species, providing direct probes of leading particle effects, and stringent constraints on models. © 2004 The American Physical Society.